Internet connectivity disruption in Kenya (Kenya) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Kenya. Data sourced from IODA.
Network Disruption Incident ID: KE-2026-0012. Severity: critical. Confidence: 65%